An Exploration of Regioselectivity During Formation of Aminoboronates from Epoxides - Trofimova, Alina; Brien, Chelsey; Tan, Joanne; Trudel, Vincent; Yudin, Andrei K. (Synlett, 2024)
α-Aminoboronic acids and their derivatives are important synthetic targets. Our research interest has been focused on the synthesis and applications of MIDA (N-methyliminodiacetic acid) protected aminoboronates. Herein we report syntheses of regioisomeric β-borylated azidoalcohols. The geminal azidoboronate represents a rare example of an α-azidoalcohol and is produced through trapping of oxonium ions that develop during the rearrangement of α-boryl aldehydes. The vicinal azidoboronate can be obtained from α-bromoacetyl MIDA boronate and enables the preparation of aziridine MIDA boronate through the Staudinger reaction.
Keywords: α-aminoboronic acids; azidoboronate; Staudinger reaction